Model Pembelajaran Mapan dalam Pembelajaran Menulis Huruf Arab pada Siswa Madrasah Ibtidaiyah - Dayudin Dayudin; Bambang Samsul Arifin (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2020)
This article aims to get an effective learning model in learning to write Arabic letters for madrasah diniyah students. This research uses the Research and Development method with 76 research subjects as madrasah ibtidaiyah students. The results obtained indicate that the Mapan learning model is very effective in achieving goals and improving learning outcomes in writing Arabic letters for students of Madrasah Ibtidaiyah. During the implementation of the learning model only faces obstacles in the form of engineering learning facilities and infrastructure. Supporting factors which are the strengths of this learning model are the awakening of student learning participation, the learning model is easy to learn and implemented by teachers and students easily follow and capture learning material.Artikel ini bertujuan untuk mendapatkan sebuah model pembelajaran yang efektif dalam pembelajaran menulis huruf Arab bagi siswa madrasah diniyah. Penelitian ini menggunakan metode Research and Development dengan subjek penelitian 76 orang siswa madrasah ibtidaiyah. Hasil yang diperoleh menunjukkan bahwa model pembelajaran Mapan sangat efektif dalam mencapai tujuan dan peningkatan hasil pembelajaran dalam menulis huruf Arab bagi siswa Madrasah Ibtidaiyah. Selama implementasi model pembelajaran hanya menghadapi kendala berupa rekayasa sarana dan prasarana pembelajaran. Faktor pendudukung yang menjadi kelebihan model pembelajaran ini yaitu membangkitkan partisipasi belajar siswa, model pembelajaran mudah dipelajari dan dilaksanakan oleh para guru dan siswa mudah mengikuti dan menangkap materi pembelajaran.